Uji Kelayakan Sistem Informasi Berbasis Web Pada Kasus Penyakit Mulut dan Kuku - Nazhifah, Sri Azizah; Basri, Fazil; Muslim, Muslim; Putri, Andrini (The Indonesian Journal of Computer Science, 2024)
Foot and Mouth Disease (FMD) is a viral infection in animals that is contagious and acute. However, public access to information and visualization of the spread of FMD and vaccination in Nagan Raya District is still limited. The reporting of FMD cases by the public still relies on village authorities, leading to inaccuracies in information and field validation constraints. Additionally, difficulties in registering livestock vaccinations are caused by inaccuracies in data and livestock location, hindering the Animal Husbandry Department in providing doses and determining the route to these locations. Therefore, this research aims to build a WebGIS that includes visualization of FMD spread, FMD case reporting, and vaccination registration. This WebGIS is developed using Laravel and Leaflet, tested with validation, reliability, and usability questionnaires. Users include the general public, the Animal Husbandry Department, and medical professionals. The results show that the WebGIS has an 89.3% feasibility percentage and is highly suitable. It can facilitate access to FMD information and visualization and streamline reporting and vaccination registration.